2022
DOI: 10.1101/2022.01.26.477791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibitory CCK+ basket synapse defects in mouse models of dystroglycanopathy

Abstract: Dystroglycan (Dag1) is a cell adhesion molecule that links the extracellular matrix to the actin cytoskeleton, and is critical for normal muscle and brain development. Mutations in Dag1 or the genes required for its functional glycosylation result in dystroglycanopathy, which is characterized by a wide range of phenotypes including muscle weakness, brain defects, and cognitive impairments. Whereas Dystroglycans role in muscle and early brain development are well defined, much less is known about its role at l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(20 citation statements)
references
References 154 publications
(334 reference statements)
0
20
0
Order By: Relevance
“…Interestingly, Briatore et al 109 performed dystrophin and Dag1 immunostaining in Purkinje neurons of the dystrophin‐deficient mdx mouse and showed that the extracellular α‐Dag1 maintains proper localization at inhibitory synapses, while the transmembrane β‐Dag1 is undetected. Another disconnect between dystrophin and Dag1 has been observed in the hippocampus, where deletion of DAG1 results in abnormal perisomatic targeting of CCK+ basket interneurons 74 . CCK+ basket interneurons in the mdx hippocampus show the same axonal mistargeting phenotype 87 .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Interestingly, Briatore et al 109 performed dystrophin and Dag1 immunostaining in Purkinje neurons of the dystrophin‐deficient mdx mouse and showed that the extracellular α‐Dag1 maintains proper localization at inhibitory synapses, while the transmembrane β‐Dag1 is undetected. Another disconnect between dystrophin and Dag1 has been observed in the hippocampus, where deletion of DAG1 results in abnormal perisomatic targeting of CCK+ basket interneurons 74 . CCK+ basket interneurons in the mdx hippocampus show the same axonal mistargeting phenotype 87 .…”
Section: Discussionmentioning
confidence: 95%
“…74,87 Glycosylation is required for neuronal migration and axon guidance, as mutations in genes within the glycosylation pathway result in a near-complete loss of glycosylation phenocopy loss of DAG1 itself. 34,69,74,85,132 However, whether glycosylation is required for Dag1 function at synapses remains unclear. In one study, DAG1 T190M mutants with significant hypoglycosylation show normal pyramidal neuron innervation by CCK+ basket interneurons in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations